2010
DOI: 10.1038/nm.2280
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of adenosine signaling in sickle cell disease

Abstract: Hypoxia can act as an initial trigger to induce erythrocyte sickling and eventual end organ damage in sickle cell disease (SCD). Many factors and metabolites are altered in response to hypoxia and may contribute to the pathogenesis of the disease. Using metabolomic profiling, we found that the steady-state concentration of adenosine in the blood was elevated in a transgenic mouse model of SCD. Adenosine concentrations were similarly elevated in the blood of humans with SCD. Increased adenosine levels promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
226
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(239 citation statements)
references
References 41 publications
6
226
0
1
Order By: Relevance
“…This signature was found to be composed of both novel and established PH candidate genes as evidenced by literature mining and the PubMed search tool. For example, ADORA2B, a candidate gene known to modify the severity of SCD (20,21), was recently identified via metabolomic profiling of a transgenic SCD mouse model with excessive adenosine signaling through the ADORA2B leading to sickling and hemolysis (22), processes known to be independently correlated with the presence of PH in SCD (13,23). Furthermore, ADC, another signature gene, which decarboxylates L-arginine to agmatine, is an established PAH candidate gene (24) and is potentially involved in SCD-related PH (25).…”
Section: Discussionmentioning
confidence: 99%
“…This signature was found to be composed of both novel and established PH candidate genes as evidenced by literature mining and the PubMed search tool. For example, ADORA2B, a candidate gene known to modify the severity of SCD (20,21), was recently identified via metabolomic profiling of a transgenic SCD mouse model with excessive adenosine signaling through the ADORA2B leading to sickling and hemolysis (22), processes known to be independently correlated with the presence of PH in SCD (13,23). Furthermore, ADC, another signature gene, which decarboxylates L-arginine to agmatine, is an established PAH candidate gene (24) and is potentially involved in SCD-related PH (25).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the obvious sickleshaped cells, we considered the reversible sickle cells with sharp and pointed protrusions and deformed cells with aberrant morphologies as sickle cells. The percentage of sickle cells of the total RBCs was calculated (Zhang et al, 2011).…”
Section: Light Microscopymentioning
confidence: 99%
“…It has been reported that the activation of the adenosine A 2B receptor may increase the deleterious effects of SCD, promoting priapism and the sickling of erythrocytes [91]. Antagonists such as MS-1706 can reverse priapism [92].…”
Section: Inherited Hemoglobin Disordersmentioning
confidence: 99%